2016
DOI: 10.1002/cplu.201600391
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Photoinduced Electron‐Transfer Reactions in a La2@Ih‐C80–Phenoxazine Conjugate

Abstract: A newly designed electron donor–acceptor conjugate consisting of an endohedral dimetallofullerene (La2@Ih‐C80) and phenoxazine (POZ) was successfully synthesized under Prato conditions. Our results document that the 1,3‐dipolar cycloaddition took place across the [5,6] junction to afford exclusively the corresponding [5,6] cycloadduct. The structure of the conjugate was characterized by means of NMR spectroscopy, absorption spectroscopy, and electrochemical studies. Computational calculations suggest that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 52 publications
2
10
0
Order By: Relevance
“…The second spectrum shows TA bands at 560 nm and 600 nm and a GSB band at 537 nm, respectively. It has been reported that the absorption of PMI •– is at 600 and 780 nm and that of the PXZ radical cation is at 540 nm . The TA band at 600 nm for the mixture of diiodo-BDP / PMI–PXZ in acetonitrile is attributed to the PMI radical anion ( PMI •– ), which is also in agreement with the spectroelectrochemistry experiments (Figures a and S10).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The second spectrum shows TA bands at 560 nm and 600 nm and a GSB band at 537 nm, respectively. It has been reported that the absorption of PMI •– is at 600 and 780 nm and that of the PXZ radical cation is at 540 nm . The TA band at 600 nm for the mixture of diiodo-BDP / PMI–PXZ in acetonitrile is attributed to the PMI radical anion ( PMI •– ), which is also in agreement with the spectroelectrochemistry experiments (Figures a and S10).…”
Section: Resultssupporting
confidence: 89%
“…It has been reported that the absorption of PMI •− is at 600 and 780 nm 64 and that of the PXZ radical cation is at 540 nm. 93 The TA band at 600 nm for the mixture of diiodo-BDP/PMI−PXZ in acetonitrile is attributed to the PMI radical anion (PMI •− ), which is also in agreement with the spectroelectrochemistry experiments (Figures 5a and S10). Similar experiments were performed in n-hexane (Figure S18), and the PMI triplet state was observed.…”
Section: Resultssupporting
confidence: 84%
“…580 nm; , this assignment is also in agreement with the spectroelectrochemical results (Figure S62a, Supporting Information). A weak shoulder ESA band at 538 nm was observed, which is in agreement with the reported PXZ radical cation absorption (535 nm) and the spectroelectrochemical data (Figure S62b, Supporting Information) . The instant appearance of this band indicated the ultrafast CS in the dyad BDP-PXZ-1 .…”
Section: Results and Discussionmentioning
confidence: 99%
“…The negative band at 700 nm is assigned to stimulated emission (SE) of the localized singlet state ( 1 StyrylBDP * ). However, no obvious absorption band of the PXZ radical cation (around 540 nm, Supporting Information, Figure S23b) and the styryl BODIPY radical anion (around 670 nm, Supporting Information, Figure S23a) were observed.…”
Section: Resultsmentioning
confidence: 99%